Altered Microstructure in Corticospinal Tract in Idiopathic Normal Pressure Hydrocephalus: Comparison with Alzheimer Disease and Parkinson Disease with Dementia - Hattori, T.; Yuasa, T.; Aoki, S.; Sato, R.; Sawaura, H.; Mori, T.; Mizusawa, H. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Previous neuropathologic studies in chronic hydrocephalus have suggested the presence of white matter damage, presumably from mechanical pressure due to ventricular enlargement and metabolic derangement. This study aimed to investigate the diffusional properties of the CST in patients with iNPH by using DTI and to determine whether this method could be used as a new diagnostic tool to differentiate patients with iNPH from those with AD and PDD and control subjects. MATERIALS AND METHODS: We enrolled 18 patients with iNPH, 11 patients with AD, 11 patients with PDD, and 19 healthy control subjects. Diffusion tensor metrics of the segmented CST, including FA values, axial eigenvalues, and radial eigenvalues, were evaluated by using tract-specific analysis. The anisotropy color-coding tractography of the CST was visually evaluated. The DTI findings were compared among groups. RESULTS: Tract-specific analysis of the CST showed that FA values and axial eigenvalues were significantly increased (P < .001), whereas radial eigenvalues were not significantly altered, in patients with iNPH compared with other subjects. The CST tractographic images in patients with iNPH was visually different from those in other subjects (P < .001). In discriminating patients with iNPH from other subjects, the CST FA values had a sensitivity of 94% and specificity of 80% at a cutoff value of 0.59. CONCLUSIONS: Our results suggest that patients with iNPH have altered microstructures in the CST. Quantitative and visual CST evaluation by using DTI may be useful for differentiating patients with iNPH from patients with AD or PDD or healthy subjects. ADAlzheimer diseaseCSTcorticospinal tractDTIdiffusion tensor imagingFAfractional anisotropyiNPHidiopathic normal pressure hydrocephalusMMSEMini-Mental State ExaminationPDParkinson diseasePDDParkinson disease with dementiaROIregion of interestSLFsuperior longitudinal fasciculus